2013
DOI: 10.4049/jimmunol.1201906
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Tumors Cease CXCL9/Mig Production as a Result of IFN-γ–Mediated Immunoediting

Abstract: During growth in the host, tumor cells are subjected to the stresses of innate and adaptive immunity (immunoediting), which provoke epigenetic changes in the tumor and increase tumor resistance to these immune responses. Our recent studies in methylcholanthrene-induced fibrosarcomas have indicated the appearance and rapid growth of tumor variants deficient in producing the T cell chemoattractant chemokine CXCL9/Mig, an important component of antitumor immunity. In the current report, we demonstrate that highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…38,39 Recently, Cxcl9 2/2 mice were reported to form large tumors due to immunosurveillance escape. 28 Thus our findings indicate that STAT2 orchestrates the expression of genes that are important in the differentiation and recruitment of immune effector cells to the tumor site.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…38,39 Recently, Cxcl9 2/2 mice were reported to form large tumors due to immunosurveillance escape. 28 Thus our findings indicate that STAT2 orchestrates the expression of genes that are important in the differentiation and recruitment of immune effector cells to the tumor site.…”
Section: Discussionmentioning
confidence: 64%
“…Bone marrow cells were differentiated into DCs with complete IMDM medium (Iscove's DMEM supplemented with 10% FBS, penicillin/streptomycin, gentamicin, and b-ME) enriched with 3.3 ng mL 21 of GM-CSF (BD Biosciences). 23 At day 6, resting DC cultures were stimulated with 100 ng mL 21 of LPS 3755 (Sigma-Aldrich), and pulsed with 5 lg mL 21 of human peptide gp100 [25][26][27][28][29][30][31][32][33] (GenScript, Piscataway, NJ) for 2 hr at 37 C.…”
Section: Generation Of Bone Marrow-derived Dendritic Cells (Bmdcs)mentioning
confidence: 99%
“…A recent study has demonstrated that cutaneous melanomas decrease CXCL9 production as a consequence of immune editing and selection of CXCL9-deficient clones (37). We have not excluded the possibility of immune editing in the metastatic-like model; however, the maintenance of Ifnγ, Cxcl9 , and Cxcl10 expression in late-stage metastases following aminophylline treatment argues against the selection and predominance of loss-of-function clones in our model.…”
Section: Discussionmentioning
confidence: 99%
“…As IFN-g has been demonstrated to have a profound effect in the immune system (25,26), both innate and adaptive immunity, …”
Section: Discussionmentioning
confidence: 99%